EXAMINATION OF THE DIFFERENCES BETWEEN ONLINE AND FACE-TO-FACE INTERVIEWS DURING A RECRUITMENT PROCESS IN TERMS OF CANDIDATES’ SELF-EFFICACY LEVELS - Zeynep Oktuğ (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In today’s work conditions, time constraints andphysical boundaries make it difficult to use face-to-face interviews during therecruitment process. Online interviews give the chance to cope with time andplace limitations, but the interaction between the candidate and theinterviewer is different than the case of sharing the same place. The aim ofthis study is to examine the differences between self-efficacy levels ofparticipants, depending on their preferences about the type of recruitmentinterview. The results of the study showed that the participants preferring anonline interview have significantly higher self-efficacy levels thanparticipants preferring a face-to-face interview. In terms of gender, womenpreferring online interview have higher self-efficacy levels than men with thesame preference. They also have higher self-efficacy than women and menpreferring face-to-face interview. Findings regarding the differences in preference ofthe type of recruitment interview are discussed.